Tax competitiveness and the fight against tax evasion: Challenges for Morocco in the era of globalization - GOURB Abdeljebare; LABDAOUI Ahmed; LAAGOUBI Mohamed; Faiza Alaoui (International Journal of Scientific Research and Innovative Studies, 2025)
The duality between tax competitiveness and tax evasion is one of the major challenges facing national and international tax authorities. The paradox of tax competitiveness and the fight against tax evasion is an area where the interests of stakeholders overlap. In a context of globalization that goes hand in hand with objectives that converge towards greater wealth, the issue of tax competitiveness and the fight against tax evasion seems to be very delicate and crucial. In this study, we will analyze the issues and factors explaining this duality and the consequences it has for the rationalization of tax competitiveness. In this context of increased tax competition and gradual harmonization of regulations, our question is as follows: In the era of globalization, how can Morocco reconcile economic attractiveness and the fight against tax evasion, while preserving its fiscal sovereignty? Our article adopts a qualitative study that explores and interprets regulatory frameworks, international agreements and administrative practices to identify the success factors and obstacles to tax competitiveness in Morocco, in order to make choices and decisions and improve the functioning and performance of the tax system in a context of globalization. Keywords: Tax competitiveness, tax evasion, international tax standards, tax sovereignty, economic attractiveness. Received Date: October 20, 2025 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/544